2019
DOI: 10.1016/j.carbpol.2019.05.063
|View full text |Cite
|
Sign up to set email alerts
|

Improving the thermal stability of different types of xylan by acetylation

Abstract: The impact of various degrees of acetylation on improving the thermal stability of xylan isolated from different botanical source has been studied; methylglucuronoxylan from birch and eucalyptus, arabinoglucuronoxylan from spruce and glucuronoarabinoxylan from sugarcane bagasse and straw. The lower molecular weight of non-acetylated methylglucuronoxylan (17.7-23.7 kDa) and arabinoglucuronoxylan (16.8 kDa) meant that they were more soluble in water than glucuronoarabinoxylan (43.0-47.0 kDa). The temperature at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…7). Its lower molar mass value observed for sdGX (4.2 kDa) in comparison to larger values reported for glucuronoxylan elsewhere (16.5-23.7 kDa) 26,64 confirmed the occurrence of a partial hydrolysis of carbohydrates during PHWE. This was also evidenced by the broader molar mass distribution observed for sdGX (DI = 3.5) (ESI, Fig.…”
Section: Role Of Lignin In the Stabilization On Emulsionsupporting
confidence: 56%
See 2 more Smart Citations
“…7). Its lower molar mass value observed for sdGX (4.2 kDa) in comparison to larger values reported for glucuronoxylan elsewhere (16.5-23.7 kDa) 26,64 confirmed the occurrence of a partial hydrolysis of carbohydrates during PHWE. This was also evidenced by the broader molar mass distribution observed for sdGX (DI = 3.5) (ESI, Fig.…”
Section: Role Of Lignin In the Stabilization On Emulsionsupporting
confidence: 56%
“…Chemical and structural characterization of GX samples, including carbohydrate and lignin compositions, acetyl groups content and molar mass were assessed according to previous publications. 15,26 Preparation of oil-in-water emulsion using wood-based stabilizers All GGM and GX samples were used to stabilize a suspension of water and hexadecane. Hexadecane, a hydrocarbon, was used as the oil phase herein instead of vegetable oil (mono-or polyunsaturated fatty acid) alternatives due to its minimal effect on the subsequent analytical method used for the assessment of the composition of stabilizers.…”
Section: Antisolvent Fractionation and Characterization Of Gx Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The first stage was between 60 and 100 °C, which was connected with the evaporation of adsorbed water. The second stage was to absorb heat for oxidative decomposition [44] . The main change parameters of the second stage were shown in Table 6 .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported that various degrees of acetylation can improve thermal stability of xylan from different plant sources and opens new avenues for the utilization of acetylated xylan from different biomass resources for use as thermoplastics and packaging [ 134 ]. Another study reported that chemical acetylation significantly improves the thermal stability of wheat bran feruloylated arabinoxylan-based biofilms without improving the mechanical or barrier properties [ 135 ].…”
Section: Importance Of Xylan Acetylation and Deacetylationmentioning
confidence: 99%